Legal Consequences Regarding Buyers Who Do Not Complete the Land Sale and Purchase Deed Process (Case Study of Supreme Court Decision Number 120 K/Pdt/2016) - Putri, Azzahra Aulia Kresna; Winanti, Atik (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
The